Unplanned Alternatives For Enteral Nutrition In Postsurgical Patients: Three Individual Cases - Yuruker, S.Savas; Topgul, Koray; Ziya Anadol, A. (Annals of Medical Research, 2021)
Aim: Enteral nutrition in surgical patients is not only physiological but also cheap. On the contrary, parenteral nutrition is more expensive and has several complications. In this report, we present three different cases in which we had to administer long term parenteral nutrition but somehow could be managed by unique applications of enteral nutrition.
Keywords: Enteral nutrition, Alternative nutrition, Postoperative nutrition.